Evaluation of Drug Utilization Pattern Using WHO Prescribing Indicators in Endodontic Department at a Tertiary Hospital in Eastern Nepal - Shrestha, Sushmita; Agrawal, Navin; Sarraf, Deependra Prasad (Birat Journal of Health Sciences, 2020)
Introduction: Irrational or inappropriate prescribing practice is common in developing countries that can lead to ineffective treatment, prolonged hospitalization, harm to the patient, increased treatment cost and development of drug-resistant organisms. The prescription of antibiotics and other drugs in endodontics is limited to patients with progressive and diffuse swelling and with systemic infection. However, antibiotics continue to be over-prescribed by more than 66% dentists without a rational justification.Therefore, the periodic assessment of drug utilization pattern is important to know the existing pattern of drug use, decrease adverse effects and provide feedback to the prescribers. Objective: To evaluate the drug utilization pattern in endodontics using the World Health Organization prescribing indicators. Methodology: A cross-sectional prospective study was conducted among the patients visiting the outpatient department of Conservative Dentistry and Endodontics. After obtaining the informed consent, the relevant data were collected on a self-designed proforma by reviewing the health cards of the patients. The WHO prescribing indicators were calculated. Descriptive statistics were calculated using SPSS version 11.0. Results: Out of 187 patients, 101 (54%) were female. Mean age was 38.9±16.6 years. Majority of the patients suffered from acute apical periodontitis (30.5%). A total of 281 drugs were prescribed to 187 patients. Paracetamol+Ibuprofen (44.1%) was the most frequently prescribed drugs. Most of the patients were prescribed one drug (78.6%). Average drug per prescription was 1.5. Majority of the drugs (89.0%) were prescribed from Essential drug list of Nepal. Conclusions: Analgesics were the most frequently prescribed drug. The prescription practice was rational. There is need to increase the number of medicine prescribed from National List of Essential medicines.Educational initiatives should be undertaken to further strengthen the rational prescription among dental practitioners.